2002
DOI: 10.1016/s1042-4431(01)00051-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost and profit efficiency in European banks

Abstract: IVIE working-papers offer in advance the results of economic research under way in order to encourage a discussion process before sending them to scientific journals for their final publication. ___________________ • The authors wish to thank David B. Humphrey for his comments and suggestions, and Juan Fernández de Guevara for his help in preparing information. The paper is part of project SEC98-0895 of the CICYT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
298
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 435 publications
(361 citation statements)
references
References 27 publications
34
298
2
10
Order By: Relevance
“…Thus, following Dietsch and Lozano-Vivas (2000), Maudos et al (2002), and others, we choose the following three outputs: loans (Q 1 ), other earning assets (Q2), and total deposits (i.e. customer and interbank) (Q3).…”
Section: Methodsologymentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, following Dietsch and Lozano-Vivas (2000), Maudos et al (2002), and others, we choose the following three outputs: loans (Q 1 ), other earning assets (Q2), and total deposits (i.e. customer and interbank) (Q3).…”
Section: Methodsologymentioning
confidence: 99%
“…Furthermore, based on these arguments, Maudos et al (2002) and Kasman and Yildirim (2006) point out that in international comparisons across a diverse group of countries and competition levels it seems more appropriate to estimate an alternative rather than a standard profit function.…”
Section: Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…Using the same function as Carbo et al, (2002) they concluded that that Italian savings banks were between 85% and 87% efficient. Maudos et al (2002) made an effort to compare cost and profit efficiencies of banks from ten countries in Europe for the period 1993-1996. The countries include Austria, Belgium, Finland, France, Germany, Italy, Luxembourg, Portugal, Spain and the UK.…”
Section: Introductionmentioning
confidence: 99%